2003
DOI: 10.1152/japplphysiol.00203.2003
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway response to electrical stimulation of the genioglossus in obstructive sleep apnea

Abstract: Contraction of the genioglossus (GG) has been shown to improve upper airway patency. In the present study, we evaluated responses in upper airway pressure-flow relationships during sleep to electrical stimulation (ES) of the GG in patients with obstructive sleep apnea. Five patients with chronically implanted hypoglossal nerve (HG) electrodes and nine patients with fine-wire electrodes inserted into the GG were studied. Airflow was measured at multiple levels of nasal pressure, and upper airway collapsibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 34 publications
8
101
1
7
Order By: Relevance
“…The severity of upper airway obstruction during sleep is related to quantitative differences in pharyngeal collapsibility, as reflected by elevations in the critical closing pressure (Pcrit). Moreover, as Pcrit fell below a minimally negative threshold of approximately 25 cm H 2 O, sleep apnea remitted, suggesting that changes in Pcrit play a pivotal role in the pathogenesis of this disorder (see Figure 1, right) (25,(57)(58)(59)(60)(61). In further studies, investigators have demonstrated that Pcrit is determined by mechanical and neural factors that regulate pharyngeal collapsibility (62)(63)(64)(65)(66)(67).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 96%
“…The severity of upper airway obstruction during sleep is related to quantitative differences in pharyngeal collapsibility, as reflected by elevations in the critical closing pressure (Pcrit). Moreover, as Pcrit fell below a minimally negative threshold of approximately 25 cm H 2 O, sleep apnea remitted, suggesting that changes in Pcrit play a pivotal role in the pathogenesis of this disorder (see Figure 1, right) (25,(57)(58)(59)(60)(61). In further studies, investigators have demonstrated that Pcrit is determined by mechanical and neural factors that regulate pharyngeal collapsibility (62)(63)(64)(65)(66)(67).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 96%
“…These increases have been attributed to decreases in pharyngeal collapsibility (14,16,17), which decreases the back pressure to inspiratory airflow (27). In previous studies, stimulating the genioglossus muscle and hypoglossal nerve led to an approximately 3-to 5-cm H 2 O decrease in critical pressure, which can account for an approximately 150-to 250-ml/s increase in maximal inspiratory airflow (18,19).…”
Section: Mechanism For Increased Airflow During Stimulationmentioning
confidence: 99%
“…Subsequently, investigators documented arousal thresholds during submental stimulation, which confounded assessment of airflow responses and limited clinical applicability of this technique during sleep (31,32). Investigators further refined the stimulation technique by inserting temporary fine-wire electrodes into lingual muscles, and demonstrated that protrusor muscle stimulation mitigated and retractor muscle stimulation worsened pharyngeal patency during sleep (13,16,18,19,33). In these prior studies, investigators scrutinized EEG and ECG signals to exclude responses associated with cortical or autonomic activation (13,18,19).…”
Section: Arousalsmentioning
confidence: 99%
See 2 more Smart Citations